Technology Education in the Quran - Rana Farras Irmi; Mohammmad Al Farabi; Ahmad Darlis (Walidem Institute and Publishing (WIP), 2023)
The type of research that the author uses is a type of qualitative research using a content analysis approach (Content Analysis), or what can be called a content study. This analysis is a research technique for making a conclusion or inference that can be replicated and the correctness of the data by considering the context. The object of this research is explored through various information in the form of books, interpretations, and journals. This journal discusses how children use technology in their early years, both at home and school. because in this increasingly sophisticated era, children cannot be separated from technology. The existence of technology is undeniable, and children cannot be prevented from using it. However, rights to property and assistance may be the best option for children. Teachers and parents alike are expected to learn a lot from the findings of this research regarding the process of using technology and its applications.